2014
DOI: 10.1159/000362779
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Prediction of Fitting Levels for Individual Cochlear Implant Recipients

Abstract: Objectives: This study analyzed the predictability of fitting levels for cochlear implant recipients based on a review of the clinical levels of the recipients. Design: Data containing threshold levels (T-levels) and maximum comfort levels (M-levels) for 151 adult subjects using a CII/HiRes 90K cochlear implant with a HiFocus 1/1 J electrode were used. The 10th, 25th, 50th, 75th and 90th percentiles of the T- and M-levels are reported. Speech perception of the subjects, using a HiRes speech coding strategy, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 63 publications
1
16
1
11
Order By: Relevance
“…Due to the preset profile used to determine the M-levels used in our clinic, no further conclusion from either M-levels or DR could be drawn from this study. Moreover, only the T-levels, in contrast to the M-levels, show a firm correlation with the degree of speech perception [van der Beek et al, 2015], and most of the correlations described in the present study were discovered using the T-levels.…”
Section: Introductionsupporting
confidence: 47%
See 4 more Smart Citations
“…Due to the preset profile used to determine the M-levels used in our clinic, no further conclusion from either M-levels or DR could be drawn from this study. Moreover, only the T-levels, in contrast to the M-levels, show a firm correlation with the degree of speech perception [van der Beek et al, 2015], and most of the correlations described in the present study were discovered using the T-levels.…”
Section: Introductionsupporting
confidence: 47%
“…Clinical research has shown a correlation between the DR and speech perception that endorses the need for setting the proper fitting levels for cochlear implants [Blamey et al, 1992;Pfingst and Xu, 2005;Pfingst et al, 2004;van der Beek et al, 2015]. The aim of the present study was to determine whether radiological data provided additional information for setting the speech processor map levels.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations